Respuesta :
First four terms would be n = 1, 2, 3, 4
f(1) = 3 ( 1 )( 1 + 3 )
= 3 * 4
=12
f(2) = 3 ( 2 )( 2 + 3 )
= 6 * 5
= 30
f(3) = 3 ( 3 )( 3 + 3 )
= 9 * 6
= 54
f(4) = 3 ( 4 )( 4 + 3 )
= 12 * 7
= 84 hope this helps!
f(1) = 3 ( 1 )( 1 + 3 )
= 3 * 4
=12
f(2) = 3 ( 2 )( 2 + 3 )
= 6 * 5
= 30
f(3) = 3 ( 3 )( 3 + 3 )
= 9 * 6
= 54
f(4) = 3 ( 4 )( 4 + 3 )
= 12 * 7
= 84 hope this helps!
f(n)=3n-1
First term,
n=1
f(1)=3(1)-1
=2
Second term,
n=2
f(2)=3(2)-1
=5
Third term,
n=3
f(3)=3(3)-1
=8
Fourth term,
n=4
f(4)=3(4)-1
=11
Therefore, the first four terms are 2,5,8,11
First term,
n=1
f(1)=3(1)-1
=2
Second term,
n=2
f(2)=3(2)-1
=5
Third term,
n=3
f(3)=3(3)-1
=8
Fourth term,
n=4
f(4)=3(4)-1
=11
Therefore, the first four terms are 2,5,8,11